The stability of the internal cavities of steel casting - I. B. Odarchenko; A. A. Sinitskij; I. N. Prusenko (Литьë и металлургия)
The mechanism and causes of the formation of casting defects, manifested in the deviation of the geometry of the internal cavities from the «cylindrical», are investigated. It is shown that the causes of distortion of the geometric shape are associated with deformation of the casting rod during thermal and mechanical interaction with the melt. Using the possibilities of computer simulation in the MAGMASOFT package, the temperature distributions of the metal in the casting body during the casting and solidification were analyzed. Areas of distortion of the geometric shape of the inner part of the casting correspond to the area of the rod subjected to the highest and longest thermal loads. The characteristics of the temperature fields in the respective zones indicate overheating of individual areas of the rod to temperatures causing phase stresses in the structure of the core mixture, sufficient for the occurrence of deformations in it. To eliminate the defect under consideration, two approaches were used to reduce the magnitude of phase stresses in the casting rod and to adjust the design of the rod tooling.